Social Polarization in the Digital Age: The Mechanism of Echo Chamber Formation and Its Impact on Social Cohesion - Zulham, Zulham (Socious Journal, 2025)
The rapid expansion of social media as a digital public sphere has fundamentally transformed patterns of social interaction and opinion formation. While social media enhances participation and access to information, it simultaneously intensifies social polarization. A key mechanism underlying this phenomenon is the echo chamber, understood as a closed communication structure that reinforces opinion homogeneity and limits exposure to alternative perspectives. This study aims to systematically analyze the mechanisms of echo chamber formation in the digital era and their implications for social cohesion. Using a Systematic Literature Review (SLR) approach following PRISMA guidelines, this research synthesizes findings from reputable academic journals addressing echo chambers, social polarization, and social cohesion. The findings indicate that echo chambers emerge through the interaction of algorithmic content personalization, users’ psychological tendencies such as confirmation bias and selective exposure, and digital network structures characterized by homophily and high clustering. Furthermore, the review demonstrates that echo chambers significantly undermine social cohesion by reducing intergroup trust, weakening bridging social capital, and intensifying affective polarization. This study concludes that social polarization in the digital era stems not from diversity of opinions, but from structural information isolation, highlighting the need for platform designs and policies that foster cross-cutting exposure and inclusive digital interaction.